2013
DOI: 10.1002/star.201300125
|View full text |Cite
|
Sign up to set email alerts
|

Starch isolation and partial characterization of commercial cooking and dessert banana cultivars growing in Mexico

Abstract: Four types of banana were collected from one of the main areas of production in the south of Mexico; three were classified as dessert bananas and one as a cooking banana. The starch was isolated from the unripe fruit, and the morphological and physicochemical features were analyzed. The isolated starches presented high purity (92–98%). The cooking banana cultivar showed the highest RS content (63.1%) following the one isolated from the dessert banana cultivar (58.1%). The morphology of the starch granules was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
21
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 29 publications
7
21
2
Order By: Relevance
“…Significant differences in the values were found among starches isolated from the banana varieties. In general, the temperature and the enthalpy values found in this work were lower than those reported using a different isolation method . Small differences in the temperatures describing the retrogradation process, were observed although the temperature range ( T c – T o ) was shorter with lower enthalpy value for this phase transition compared to published data .…”
Section: Resultscontrasting
confidence: 82%
See 2 more Smart Citations
“…Significant differences in the values were found among starches isolated from the banana varieties. In general, the temperature and the enthalpy values found in this work were lower than those reported using a different isolation method . Small differences in the temperatures describing the retrogradation process, were observed although the temperature range ( T c – T o ) was shorter with lower enthalpy value for this phase transition compared to published data .…”
Section: Resultscontrasting
confidence: 82%
“…The breakdown, setback, and peak viscosity obtained from the pasting profile in both studies showed differences, indicating that the starch isolation method influenced the pasting characteristics. Starch purity as reported by Agama-Acevedo et al [13] was found between 92.08 and 98.63%; meanwhile, in this work, the purity values ranged from 82.82 to 89.56% (Macho 88.89%, Enano 83.75%, Morado 82.82%, and Valery 89.56%). The isolation method used in this study is a simple procedure yielding a product with lower purity, although the obtained starches showed suitable properties to be used as a food ingredient.…”
Section: Pasting Formationsupporting
confidence: 65%
See 1 more Smart Citation
“…The DSC curves of red adzuki bean starches exhibited wider peaks than those from other three legume starch (Figure ), which suggested its broader range of gelatinization temperature (Δ T r ) as shown in Table . The Δ T r is related to the heterogeneity of the starch granule sizes and the distribution of amylose and amylopectin, which produce a semi‐crystalline arrangement inside the granule (Agama‐Acevedo et al., ). A wide melting range might imply crystals with a large variation in stability, whereas a narrow range could suggest crystals of a more homogeneous quality and similar stability.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the molecular and structural features of banana starch are different for each variety [30]. This issue can be related to the consumption type, as previously reported [31][32][33]. The banana variety influences the crystalline arrangement because the chain-length distribution is important during chemical modification of starch.…”
Section: Pasting Profilementioning
confidence: 91%